Biomaterials for corneal bioengineering. (6th March 2018) - Chen, Zhi; You, Jingjing; Liu, Xiao; Cooper, Simon; Hodge, Christopher; Sutton, Gerard; Crook, Jeremy M; Wallace, Gordon G
Abstract: Corneal transplantation is an important surgical treatment for many common corneal diseases. However, a worldwide shortage of tissue from suitable corneal donors has meant that many people are not able to receive sight-restoring operations. In addition, rejection is a major cause of corneal transplant failure. Bioengineering corneal tissue has recently gained widespread attention. In order to facilitate corneal regeneration, a range of materials is currently being investigated. The ideal substrate requires sufficient tectonic durability, biocompatibility with cultured cellular elements, transparency, and perhaps biodegradability and clinical compliance. This review considers the anatomy and function of the native cornea as a precursor to evaluating a variety of biomaterials for corneal regeneration including key characteristics for optimal material form and function. The integration of appropriate cells with the most appropriate biomaterials is also discussed. Taken together, the information provided offers insight into the requirements for fabricating synthetic and semisynthetic corneas for in vitro modeling of tissue development and disease, pharmaceutical screening, and in vivo application for regenerative medicine.